2018
DOI: 10.3390/molecules23081998
|View full text |Cite
|
Sign up to set email alerts
|

DPP-IV Inhibitory Potentials of Flavonol Glycosides Isolated from the Seeds of Lens culinaris: In Vitro and Molecular Docking Analyses

Abstract: Dipeptidyl peptidase IV (DPP-IV), a new target for the treatment of type 2 diabetes mellitus, degrades incretins such as glucagon-like peptide 1 (GLP-1) and glucose-dependent insulinotropic polypeptide. DPP-IV inhibitors shorten the inactivation of GLP-1, permitting the incretin to stimulate insulin release, thereby combating hyperglycemia. In our ongoing search for new DPP-IV inhibitors from medicinal plants and foods, three flavonol glycosides (1–3) were isolated from the seeds of Lens culinaris Medikus (Fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 24 publications
1
61
0
1
Order By: Relevance
“…Extensive studies on the phytochemical-based DPP-IV inhibitors were undertaken in the literature [ 19 , 20 , 21 ], and in our previous studies [ 16 , 22 ]. Flavonoids and phenolic compounds were found to be the DPP-IV inhibitors with potent to mild activities, showing IC 50 values in the range of 0.12 to 63.26 μM.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Extensive studies on the phytochemical-based DPP-IV inhibitors were undertaken in the literature [ 19 , 20 , 21 ], and in our previous studies [ 16 , 22 ]. Flavonoids and phenolic compounds were found to be the DPP-IV inhibitors with potent to mild activities, showing IC 50 values in the range of 0.12 to 63.26 μM.…”
Section: Resultsmentioning
confidence: 99%
“…The five factors that affect diabetes treatment are dipeptidyl peptidase- IV (DPP-IV), α-glucosidase inhibitors, aldose reductase (ALR) inhibitors, phatase 1B (PTP1B) inhibitors and peroxisome proliferator-activated receptor-γ (PPAR-γ) [ 15 ]. Recently, incretin-based therapies for the treatment of type 2 diabetes mellitus have begun to appear, one of which is DPP-IV inhibitors [ 16 ]. The incretin system includes glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP), which in response to high blood sugar levels induce the release of insulin from the pancreatic β-cell [ 13 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, S. platensis significantly (P < 0•05, P < 0•01 and P < 0•001) inhibited DPP-IV enzyme activity, indicating that butanol fraction can enhance endogenous glucagon-like peptide 1 and glucose-dependent insulinotropic polypepide activity. A recent study has shown that flavonol glycosides from the seeds of Lens culinaris Medikus (Fabaceae) inhibited DPP-IV enzyme activity in the dose-dependent manner (48) . Therefore, it is anticipated that the same phytochemical constituents of S. platensis may be responsible for the observed DPP-IV inhibitory activity effect.…”
Section: Discussionmentioning
confidence: 99%